Kepemimpinan Transformasional Terhadap Prestasi Kerja dan Disiplin Kerja - Zahrawanni Niza Gunarko Putri; Diding Nurdin; S Suryadi (Universitas Pendidikan Indonesia, 2023)
This study aims to determine the relationship of transformational leadership to work performance and work discipline in the Field of High School Development. The method used is descriptive research with a quantitative approach. The data collection technique used a closed questionnaire in the form of a google form and a questionnaire distributed to 37 PSMA employees. Based on the results of data testing, the correlation coefficient between variable X and variable Y1 is 0.176. While the results of the correlation coefficient between variables X and Y2 of 0.560. This shows that the correlation between the three variables, namely variable X, variable Y1, and Variable Y2 is at the level of a positive relationship. The conclusion of this study is that the relationship between the transformational leadership of the head of the field on work performance and work discipline at the West Java Provincial Education Office is good.